Índices de qualidade da água e de estado trófico do rio Caiabi, MT - Andrietti, Grasiane; Freire, Rosane [UNESP]; do Amaral, Adriana Garcia; de Almeida, Frederico Terra; Bongiovani, Milene Carvalho; Schneider, Roselene Maria (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2016)
The objective of this study was to evaluate the water quality of the Caiabi River based upon the water quality index (WQI) and the trophic state index (TSI), considering seasonal and spatial variations, with the aim of determining the most appropriate monitoring design for this study site. Sampling for water quality monitoring was conducted at five points on theCaiabi River from July 2012 to June 2013. Quality parameters quantified were as follows: pH, temperature, conductivity, dissolved oxygen, total and thermotolerant coliforms, turbidity, Kjeldahl nitrogen, nitrite, nitrate, total phosphorus, biochemical oxygen demand, series of solids, and chlorophyll a. Sampling procedures and analysis followed the methods recommended by the Standard Methods for the Examination of Water and Wastewater. The WQI results showed that the quality of the Caiabi River water is good. TSI results demonstrated the low risk of eutrophication in the Caiabi River, indicating an ultra- oligotrophic lotic environment. Analysis of variance showed that 10 of the 16 monitored quality parameters presented differences of means between the dry and rainy seasons or among the monitored points or in the interaction between seasons and points. These results indicate that two annual sampling collections at two points may be sufficient to describe the water quality behavior in the basin, as long as the conditions of land use are stable.
Water quality index and eutrophication indices of Caiabi River, MT
Keywords: Amazon basin; Soil use and management; Surface water; Water resources